Linking microbial ecology to the cycling of neutral and acidic polysaccharides in pustular mats from Shark Bay, Western Australia - Skoog, Emilie J.; Cutts, Elise; Bosak, Tanja (Frontiers in Microbiology, 2025)
Cyanobacteria and other microbes in peritidal microbial mats have produced extracellular polymeric substances (EPS) for more than two billion years. The production and degradation of EPS contributes to the biogeochemical cycling of carbon and carbonate precipitation within modern microbial mats, but key microbes involved in the cycling of EPS remain unidentified. Here, we investigate the cycling of EPS in the peritidal pustular mats of Shark Bay, Western Australia. We characterize the chemical composition of EPS produced by cyanobacterial enrichment cultures under natural and UV-stress conditions and link these findings to the metabolic potential for EPS production and degradation encoded in 84 metagenome-assembled genomes (MAGs) from the mat community. We further identify the key microbial degraders of specific acidic and neutral polysaccharides in this community by cultivating enrichment cultures on seven commercially available polysaccharides representative of those present in the mats and assessing the dominant taxa. All sequenced Cyanobacteria MAGs have the potential to synthesize mannose, fucose, glucose, arabinose, rhamnose, galactose, xylose, N-acetylglucosamine, galacturonic acid and glucuronic acid. Biochemical analyses confirm the presence of nearly all these monosaccharides in the hydrolysates of EPS extracted from UV- and non-UV exposed cyanobacterial enrichments. Ultraviolet radiation influences the structure and composition of EPS by reducing the hydration, potentially due to cross-linking among polymers in EPS and increasing the relative abundances of uronic acids and xylose in polysaccharides. Analyses of carbohydrate-active enzymes (CAZymes) in the MAGs and of 16S rRNA sequences from experimental polysaccharide enrichments point to major roles for Bacteroidetes, Planctomycetes, and Verrucomicrobia in the cycling of acidic EPS. These experiments reveal a complex interplay among microbial community composition, CAZyme diversity, environmental stressors, and EPS cycling, which together shape carbon flow and biomineralization in pustular mats in Shark Bay.